Design at the service of health - Vargas, David; Larsen, Christian; Cabello, Andrea (Base Diseño e Innovación, 2015)
The creation of copper railings for clinical beds is one of the main innovations of duam, a Chilean company, under the brand name Copperbiohealth. Like other products that use copper, the purpose is to take advantage of the antimicrobial properties of this metal in health facilities and public spaces.